Exotic plants used therapeutically by Bapedi traditional healers for respiratory infections and related symptoms in the Limpopo Province, South Africa - Semenya, S. S.; Maroyi, Alfred (Indian Journal of Traditional Knowledge, 2018)
The present study examines the use of exotic plants by Bapedi healers (THs) as medicine for respiratory infections (RIs) and related symptoms.A sample....
Article published in the Indian Journal of Traditional Knowledge; vol 17 (4).pp 663-671
Keywords: Bapedi healers; Exotic plants; Limpopo Province; Respiratory infections; Exotic plants; Respiratory infections-Alternative treatment